Born or not: A moderated mediation model of the relationship between work-family conflict and female employees' wellbeing based on fertility intention during the COVID-19 pandemic - Zeng, Zhen; Ma, Jian; Ma, Yueru; Li, Dayuan; Sun, Yong (Frontiers in Public Health, 2023)
The previous academic research on work-family conflict mainly focused on the relevant elements in the work field. This study concludes that elements of the family domain have a significant impact on the relationship between work-family conflict and employee wellbeing. Female employees' perceptions of wellbeing largely depend on their willingness to have children when they take on family roles. During COVID-19, employees had more time to fulfill both work and family roles in the family sphere due to the epidemic blockade, the contribution of the female employee's significant other (husband) in family matters had a significant impact on Fertility intention. This study using SPSS 24.0 AMOS 20.0 and M plus 7.4 statistical analysis tools to test the proposed hypotheses. In the paired data of 412 working female employees and husbands of Chinese dual-earner families with different occupational backgrounds, hypothesis testing results support that female employees' work → family conflict is negatively related to female employees' fertility intentions, and female employees' fertility intentions are positively related to wellbeing; female employees' family → work conflict is negatively related to female employees' wellbeing; husband's flexible work stress is negatively related to husband's share of housework; husband's share of housework moderated the front, rear and overall mediating effects by the fertility intention. When formulating policies, the managers should consider not only the direct effects of policies, but also the indirect effects that policies may have on other family members of employees. Managers should develop management policies during an epidemic that are more responsive to the actual needs of employees during an epidemic. The management of female employees should give due consideration to the family status of female employees and the enterprises should recognize the importance of childcare for female employees.